2016
DOI: 10.1021/acsami.6b04555
|View full text |Cite
|
Sign up to set email alerts
|

Rice (Oryza sativa L.) Seed Sterilization and Germination Enhancement via Atmospheric Hybrid Nonthermal Discharge Plasma

Abstract: We designed a system to produce atmospheric hybrid cold-discharge plasma (HCP) based on microcorona discharge on a single dielectric barrier and applied it to inactivate microorganisms that commonly attach the rice seed husk. The cold-plasma treatment modified the surface of the rice seeds, resulting in accelerated germination and enhanced water imbibition. The treatment can operate under air-based ambient conditions without the need for a vacuum. The cold-plasma treatment completely inactivated pathogenic fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(142 citation statements)
references
References 31 publications
4
132
0
Order By: Relevance
“…Plasma treatment can have a variety of effects on the morphology of seeds due to its complex interaction with organic materials and living cells. Another consequence of the plasma treatment is the modication of surface properties and sterilization of the seeds as reported by Khamsen et al 20 and Basaran and Akhan.…”
Section: 10mentioning
confidence: 92%
See 1 more Smart Citation
“…Plasma treatment can have a variety of effects on the morphology of seeds due to its complex interaction with organic materials and living cells. Another consequence of the plasma treatment is the modication of surface properties and sterilization of the seeds as reported by Khamsen et al 20 and Basaran and Akhan.…”
Section: 10mentioning
confidence: 92%
“…3,4,37,38 The improved germination by plasma discharge on the seed surface can be correlated to several factors such as increase in surface wettability, 14 killing of bacteria and pathogens on the seed surface. 20,21 In addition, the local heating probably opens up the seed coating and increases the water intake. The plasma discharge produced RONS such as O 3 , N 2 O and electrons have modied the water uptake rate and increased the germination metabolisms.…”
Section: 37mentioning
confidence: 99%
“…Common gases used include air, modified air (Shi et al ., ) or noble gases such as argon (Khamsen et al ., ). The efficacy of CP is highly variable depending on the feed gas.…”
Section: Cold Plasma Overviewmentioning
confidence: 97%
“…In general, pathogen inactivation efficacy increases with the increase in exposure to CP (Lu et al ., ; Herceg et al ., ). The distance of the produce or pathogen from the CP source also differs, ranging from 1 to 20 cm in in vivo experiments (Hayashi et al ., ; Khamsen et al ., ), and 0.5 to 1.5 cm in most in vitro studies (Panngom et al ., ; Herceg et al ., ; Table ). It is hypothesized that CP treatment duration and distance are correlated, as most reports (both in vivo and in vitro ) have demonstrated that longer distances required longer durations of CP treatment for effective pathogen inactivation (e.g.…”
Section: Cold Plasma Prospects and Constraintsmentioning
confidence: 99%
See 1 more Smart Citation